(untitled) (Journal of the College of Education for Women, 2019)
In children "dependency" appears during the pre-school age ,Assoon as the child begins to distinguish people surrounding him, he tends to be aware of certain people and tries purposefully to draw their attention . This dependency develops and is reinforced as the child s family shows her tendency to help the child in all what he does any task .Therefore as it seems that the extent to which a child becomes dependent or independent relies on a number of interrelated variables which are usually put together in one formation . The two researchers have chosen three variables used in studying comparing and measuring the aspects of dependent behavior . These chosen variables are (1) The child s sex (2) The child s ordinal position in the family and (3) The mothers job Here emerges the importance of the problem discussed at this research and to what extent it was vital to know the "aspects of dependent behavior "and the relation that bounds these aspects to the variables mentioned above . Such research paper is mainly needed for establishing the way by which we can treat the aspects of dependent behavior in children . This precise research aims at recognizing the aspects of dependent behavior and their relation to some variables . This was to be achieved by examining three zero – assumption . The sample included (81) children in the kindergartens age who are chosen frome a number of special nursery schools (kindergartens) in Baghdad frome AL-Rusafa and AL-Karkh . The average of their ages ranged between (4– 5) years old . The instrument chosen to measuring the aspects of dependent behavior related to children was given to parents .It contained four major skills and each skill was underlined by a number of related items . When reaching the step of using statistical analysis , the analysis of variance , the – test formula and the person s correlation were used . The results showed that there are certain statistically significant differences in the aspects of dependent behavior between males and females and that the dependent behavior is more apparent in females than in males . The results have also shown that males tend to become more independent as they grow older , because they will no more consult their mothers as they used to do during the earlier stage of their childhood . Father , males tend to discover their environment by their own independently of their parents . We can expect at the furthermost that in future , there might happen a wider change in the behavior of the coming generations of males and females in term of their dependency and independency . As the results have shown , in respect to the child s ordinal position in his family , that this has no influence in showing the dependent behavior whether he is the first second or third in the family . The third variable , that s the mother s job and as the results have shown has statistically significant differences in showing the aspects of dependent behavior between the working mother s children and the children of an unemployed mother ; ie ; a housewife . This illustrates that the work of a mother outside the house makes it more possible for here child to depend on his own self, in other word, it will develop his independency .